Additional records of osmiine bees (Hymenoptera: Megachilidae: Osmiini) from Azerbaijan - Proshchalykin, Maxim Yu.; Maharramov, Mahir M. (Acta Biologica Sibirica, 2020)
Data on 38 species and four subspecies of three genera of the tribe Osmiini (Megachilidae) collected in Nakhchivan Autonomous Republic of Azerbaijan are presented. Of them, 19 species and one subspecies are recorded for the fauna of Azerbaijan for the first time. This paper is based on the material of more than 155 specimens, collected by the authors in June 2019 in 21 localities of the republic. Additional 44 specimens of Osmiini from the Nakhchivan Autonomous Republic stored in the collection of the Institute of Zoology of the National Academy of Sciences of Azerbaijan, Baku have also been studied. Currently, 64 species and four subspecies of osmiine bees are known from this country. This is distinctly less in comparison with the adjacent fauna of Turkey (247), Turkmenistan (110) and Iran (88), but more than understudied faunas of Georgia (31) and Armenia (44). It is assumed that the number of Osmiini species in Azerbaijan may be at least twice as large.